Contributions to Turkish Flora: Taxonomic and distributional notes on the poorly known Noccaea (Brassicaceae) species - Özgi̇şi̇, Kurtuluş; Özüdoğru, Bariş; Ocak, Ati̇la (Phytotaxa, 2018)
Herein the taxonomical status of some poorly known Noccaea (Brassicaceae) species is revised. Moreover, the morphological, distributional and ecological properties of these species are updated. Some overlooked species in Turkey such as Noccaea versicolor and N. aptera are recollected and their descriptions emended and discussed. N. huber-morathii is also recollected from its type locality after its first collection. The description and distribution of N. huber-morathii are also updated. New distribution areas for N. tatiaae and N. aghrica, which have been insufficiently known species in Turkey, are also given.